The Effect of Cold Swaging Deformation on the Microstructures and Mechanical Properties of a Novel Metastable β Type Ti–10Mo–6Zr–4Sn–3Nb Alloy for Biomedical Devices - Cheng, Jun; Wang, Hongchuan; Li, Jinshan; Gai, Jinyang; Ru, Jinming; Du, Zhaoxin; Fan, Jiangkun; Niu, Jinlong; Song, Hongjie; Yu, Zhentao (Frontiers in Materials, 2020)
This work investigated the microstructures, texture evolution, and mechanical properties of newly designed metastable β type Ti–10Mo–6Zr–4Sn–3Nb (wt.%) alloys for biomedical devices, which were subjected to cold swaging deformation with reductions of 15–75%. With the increment in the reduction of swaging deformation, the grains are broken and gradually refined, and stress-induced martensite transformation takes place, resulting in the formation of the α” phase. Moreover, the 1 1 2 <1 1 1> and 1 1 0 <1 1 2> fibers turn into γ-fiber 1 1 1 <1 1 0> and α-fiber 1 1 2 <1 1 0> with the increment in the swaging reduction. The α-fiber texture in particular, first weakens and then strengthens during cold deformation. Under the combined effect of sub-structures, grain refinement, and texture evolution, the strength of the alloy is gradually enhanced with the increment in the cold deformation reduction. The solution-treated alloy bar shows superior cold workability in the swaging process. The plasticity remains at a moderate level because the initial grains have not been completely broken at the beginning of cold swaging deformation. The elastic modulus of the alloy shows a downward trend with an increasing reduction, which is related to the dislocation multiplication, grain refinement, and grain orientation evolution during cold swaging deformation.